Investigation of The Anticarcinogenic Effects of Portulaca oleracea Extracts on Different Human Cancer Cell Lines - Sandal, Suleyman; Keser, Serhat; Tekin, Suat; Keser, Fatma; Turkoglu, Ismail; Karatepe, Mustafa (Wiley, 2017)
[Abstract Not Available]